Antibacterial test of various ingredients of “Indonesian Jamu” - Selva Rosyta Dewi, .- (AIP Publishing., 2019)
Jamu is an Indonesian traditional beverage, made from various Indonesian spices, and believed to possess antibacterial properties. The aim of this research was to determine whether typical Indonesian Jamu ingredients had antibacterial compounds. The study was performed to determine the activity of the filtrate of various ingredients in inhibiting Staphylococcus aureus ATCC 25922 and Escherichia coli ATCC 25923 growth. Ingredients used in Jamu were Alpinia galanga, Zingiber officinale, Curcuma domestica, Tamarindus indica, Kaempferia galanga, Curcuma xanthorrhiza, Syzygium aromaticum, Syzygium polyanthum, Myristica fragrans, Cinnamomum burmannii, Cymbopogon citratus, and Boesenbergia pandurata. The concentration used for the respective filtrates was 10% (w/v). Filtrates were made according to common Jamu production, i.e. by blending the ingredients together with distilled water. Sensitivity tests were done by agar diffusion method. Qualitative analysis based on diameter of inhibition zone was conducted to determine the antibacterial activity of all Jamu ingredients. Results showed that the Jamu ingredient with the best antibacterial content for inhibiting E. coli was Kaempferia galanga (9 mm), while for inhibiting S. aureus it was Tamarindus indica (8 mm). The results indicate that Jamu ingredients have antibacterial compounds as expected by most Indonesian people.